The Boechera model system for evolutionary ecology. Issue 11 (13th November 2022) - Rushworth, Catherine A.; Wagner, Maggie R.; Mitchell‐Olds, Thomas; Anderson, Jill T.
Abstract: Model systems in biology expand the research capacity of individuals and the community. Closely related to Arabidopsis, the genus Boechera has emerged as an important ecological model owing to the ability to integrate across molecular, functional, and eco‐evolutionary approaches. Boechera species are broadly distributed in relatively undisturbed habitats predominantly in western North America and provide one of the few experimental systems for identification of ecologically important genes through genome‐wide association studies and investigations of selection with plants in their native habitats. The ecologically, evolutionarily, and agriculturally important trait of apomixis (asexual reproduction via seeds) is common in the genus, and field experiments suggest that abiotic and biotic environments shape the evolution of sex. To date, population genetic studies have focused on the widespread species B. stricta, detailing population divergence and demographic history. Molecular and ecological studies show that balancing selection maintains genetic variation in 10% of the genome, and ecological trade‐offs contribute to complex trait variation for herbivore resistance, flowering phenology, and drought tolerance. Microbiome analyses have shown that host genotypes influence leaf and root microbiome composition, and the soil microbiome influences flowering phenology and natural selection. Furthermore, Boechera offers numerous opportunities for investigating biological responses to global change. In B. stricta, climate change has induced a shift of >2 weeks in the timing of first flowering since the 1970s, altered patterns of natural selection, generated maladaptation in previously locally‐adapted populations, and disrupted life history trade‐offs. Here we review resources and results for this eco‐evolutionary model system and discuss future research directions.